The Implementation of a Merit System in Promotion and Job Rotation at the Kuningan District Civil Service and Human Resource Development Agency - Muhammad Angga Ramdani; Ayu Barokah; Sri Wulandari; Farida Nurfalah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Kuningan District has been awarded the Meritocracy award with a good predicate. This award is given to assess the implementation of the merit system in the management of civil servants for local government agencies. The Kuningan District Civil Service and Human Resource Development Agency are expected to continue innovating in enhancing the implementation of the merit system. The method used in this research is qualitative research. Researchers conducted research using interview techniques. The theory used is the merit system theory according to Grundman in the U.S. Merit System Protection Board (2016). There are 9 indicators in the implementation of the merit system, namely Recruitment, Selection, and Advancement, Equity, Compensation, Conduct, Utilization, Retention, Employee Training and Development, Neutrality, Public Interest. The implementation of promotions and job rotations in the Kuningan District Civil Service and Human Resource Development Agency has applied the merit system. In its implementation, educational background, work record, and relevant skills also become specific requirements for a civil servant who will undergo promotions and job rotations. The research results show that the Kuningan District Civil Service and Human Resource Development Agency have optimized promotions and job rotations in accordance with the merit system.